2021
DOI: 10.1093/femsle/fnab044
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of undecylprodigiosin biosynthesis in the yeast-scavenging Streptomyces strain MBK6

Abstract: Streptomyces are efficient chemists with a capacity to generate diverse and potent chemical scaffolds. The secondary metabolism of these soil-dwelling prokaryotes is stimulated upon interaction with other microbes in their complex ecosystem. We observed such an interaction when a Streptomyces isolate was cultivated in a media supplemented with dead yeast cells. Whole-genome analysis revealed that Streptomyces sp. MBK6 harbours the red cluster that is cryptic under normal environmental conditions. An interactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 42 publications
(29 reference statements)
0
6
0
Order By: Relevance
“…2, 22.8, 28.4, 29.2, 29.4-29.7, 32.0, 58.9, 93.7, 112.3, 112.7, 116.6, 118.8, 128.7, 130.1, and 171.6. Based on interpretation of the MS and 1D NMR spectroscopic data and comparison of the NMR data to previous reports (Bikash et al, 2021), compound 1 was identified as undecylprodigiosin.…”
Section: Identification Of Undecylprodigiosinmentioning
confidence: 74%
See 2 more Smart Citations
“…2, 22.8, 28.4, 29.2, 29.4-29.7, 32.0, 58.9, 93.7, 112.3, 112.7, 116.6, 118.8, 128.7, 130.1, and 171.6. Based on interpretation of the MS and 1D NMR spectroscopic data and comparison of the NMR data to previous reports (Bikash et al, 2021), compound 1 was identified as undecylprodigiosin.…”
Section: Identification Of Undecylprodigiosinmentioning
confidence: 74%
“…The NMR spectrum of compound 1 displayed proton signals at δ H 7.28 (1H), 7.01 (s, 1H), 6.97 (1H), 6.85 (1H), 6.37 (1H), 6.21 (1H), 6.10 (s, 1H), 4.02 (s, 3H, O-CH3), 2.79 (s, 2H), 1.21-1.26 (m, 20H), and 0.86 (s, 3H) and carbons at δ C 14.2, 22.8, 28.4, 29.2, 29.4-29.7, 32.0, 58.9, 93.7, 112.3, 112.7, 116.6, 118.8, 128.7, 130.1, and 171.6. Based on interpretation of the MS and 1D NMR spectroscopic data and comparison of the NMR data to previous reports ( Bikash et al ., 2021 ), compound 1 was identified as undecylprodigiosin.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Propylprodigiosin-producing bacteria have not been reported to the best of our knowledge, and we are yet to lay our hands on a report on prodigiosin-producing Brevidomonas olei . However, literature has suggested different derivatives of prodigiosin such as prodigiosin (2-methyl-3-pentyl-6-methoxyprodiginine), undecylprodigiosin metacycloprodigiosin, streptorubin B, and cycloprodigiosin (Bikash et al 2021 ; Habash et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Close physical contact and environmental signals between microorganisms in the soil microbiome have been shown to initiate cascades of reactions that elicit the production of secondary metabolites 11,12 . Indeed, direct physical contact between various Streptomyces species and several microorganisms stimulates Streptomyces to produce undecylprodigiosins 13,14 . Gamma-butyrolactones and even select antibiotics are important chemical signals for intraspecies communication and regulation of gene expression in Streptomyces 6 .…”
Section: Introductionmentioning
confidence: 99%